Backward-Sloping Labor Supply Functions in Dual Economies–The Africa Case - Berg, Elliot J. (Quarterly Journal of Economics, 1961)
Introduction, 468. — I. The dual economy and the migrant labor system, 470. — II. The individual's offer of labor, 472. — III. The supply of labor to the exchange economy as a whole, 480; the level of village income and the supply of labor, 480; the rate of wages and the supply of labor in the exchange sector, 485. — IV. The supply of labor to the territory, 489. — V. Summary and conclusions, 491.